Optimalisasi Produktivitas Lini Assembling Menggunakan Metode PDCA Pada Industri Otomotif - Pepen Komarudin; Nasrun Baldah (Universitas Dharmawangsa, 2026)
This study aims to analyze productivity improvements during the Start of Production (SOP) stage through the implementation of the Plan-Do-Check-Act (PDCA) method in an automotive manufacturing industry located in the GIIC Cikarang industrial area. The research focuses on the inability to achieve the production efficiency target of 95% due to limitations in workforce skills, production facility reliability, and component inventory management. The research method used was descriptive with a case study approach through observation, interviews, documentation, and analysis of production reports and Andon system data. The PDCA cycle was implemented systematically through problem identification, corrective action implementation, evaluation, and continuous improvement standardization. The results showed that the implementation of PDCA improved production process stability, reduced line stop disturbances, and increased work efficiency and productivity during the SOP stage. This research is expected to serve as a reference for manufacturing companies in implementing continuous improvement to enhance operational performance